INFLUENCE OF LACTOBACILLUS SPP. ON COLONIZATION AND ANTI-INFECTIOUS RESISTANCE OF THE MUCOUS MEMBRANES OF THE UPPER RESPIRATORY TRACT - Kalinichenko, S. V.; Korotkykh, O. O.; Pokhil, S. I.; Bakumenko, M. G. (International Journal of Medicine and Medical Research, 2017)
Background. Lactobacilli are very important for the formation of colonization resistance and have pronounced antagonistic effect against a wide range of microorganisms. That is why the lactobacilli have extensive use as a component of classic probiotic agents that are widely used to prevent and treat dysbiotic conditions of digestive and genital systems of people. Objective. The aim of the research was to study the effect of lactobacilli on anti-infectious resistance of mucous membranes of upper respiratory tract. Methods. The colonization degree (lg CFU / g) of nasal mucosal membranes by Lactobacillus spp. and S. aureus was determined in all carriers before the experiment. Also, the level of lysozyme and secretory immunoglobulin A (sIgA) in nasal secretions cavities was identified. Results. It was established a clear dysfunction of anti-infectious resistance in carriers of Staphylococcus aureus - a decrease of colonization resistance and local immunity of mucous membranes of upper respiratory tract. As for the anti-infectious resistance of nasal mucosal of S. aureus carriers, the level of lysozyme and secretory immunoglobulin A gradually increased after the application of probiotic strain L. rhamnosus GG, and in 21 days it reached rates of healthy individuals. Conclusions. It was found out that probiotics for nasal passages sanitation in Staphylococcus aureus carriers lead to gradual eradication of the pathogen (S. aureus) with restoration of colonization and anti-infectious resistance, mucous membranes and upper respiratory tract.